2014
DOI: 10.1103/physreva.90.041601
|View full text |Cite
|
Sign up to set email alerts
|

Direct probe of topological order for cold atoms

Abstract: Cold-atom experiments in optical lattices offer a versatile platform to realize various topological quantum phases. A key challenge in those experiments is to unambiguously probe the topological order. We propose a method to directly measure the characteristic topological invariants (order) based on the time-of-flight imaging of cold atoms. The method is generally applicable to detection of topological band insulators in one, two, or three dimensions characterized by integer topological invariants. Using detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
1
39
0
1
Order By: Relevance
“…The Berry phase of a 2D DTP can be directly measured using an interferometric approach in momentum space [38]. Moreover, it has been demonstrated that the full tomography of Bloch states (vectors) can be achieved with cold atoms in optical lattices to reveal the band topology [72][73][74][75][76][77], which would be applicable in our proposed system.…”
Section: Realization and Detection In Optical Latticesmentioning
confidence: 99%
“…The Berry phase of a 2D DTP can be directly measured using an interferometric approach in momentum space [38]. Moreover, it has been demonstrated that the full tomography of Bloch states (vectors) can be achieved with cold atoms in optical lattices to reveal the band topology [72][73][74][75][76][77], which would be applicable in our proposed system.…”
Section: Realization and Detection In Optical Latticesmentioning
confidence: 99%
“…In experiment, one discretizes the BZ and a pixelized version ofŜ(k) can be obtained through time-of-flight imaging. Refs [61,62] describe in detail how to measureŜ(k) in experiment. One astute observation [62] was that the spin component is related to the density distributions aŝ S z (k) = [n ↑ (k) − n ↓ (k)]/[n ↑ (k) + n ↓ (k)].…”
mentioning
confidence: 99%
“…For the simplest case of p = q = 1, we numerically diagonalize the realistic real-space Hamiltonian and compute the corresponding Hopf index for different h based on the method introduced in Ref. [61]. Our results are summarized in Table I.…”
mentioning
confidence: 99%
“…Due to the periodicity of the momentum space Hamiltonian, the Brillouin zone can be regarded as a two-dimensional torus. Remarkably, the field strengths F 12 (k l ) can also be directly measured by using time-of-flight imaging [57]. We found that the Chern number for the lowest band is c 3 = 2.…”
Section: Resultsmentioning
confidence: 85%